RESEARCH ON ELASTIC-RING ISOLATOR’S DAMPING BASED ON PIEZOELECTRIC SHUNT DAMPING TECHNIQUE - YIN Shuang; WEN LiHua; LIU Yong (Jixie qiangdu)
To analyze the present problems of the elastic-ring isolator,such as the unideal damping effect,the unadjustable damping and so on,the piezoelectric shunt damping technique was adopted to study the vibration control performance of the elastic ring.Using piezoelectric film as a substitute for the damping material of the elastic-ring isolator,the elastic-ring piezoelectric shunt damping isolator was designed.Moreover,shunt circuit was designed which was based on the gyrators and the piezoelectric shunt damping system electromechanical coupling model was established to study the method of optimizing parameters of the shunt circuit.Furthermore,the optimal parameters were determined.Finally,the vibration control performance of the piezoelectric shunt damping system was experimentally analyzed.Experimental results show that the vibration of the structure can be reduced by 9 d B.